Response of Vermicompost on Seedling Growth and Quality Parameters of Juniperus polycarpos C. Koch under Nursery Condition - Negi, P.S.; Sharma, Sandeep; Thakur, Neha (Annals of Arid Zone, 2023)
A trial was conducted to study the effect of different doses of vermicomposton the seedling growth and quality parameters of Juniperus polycarpos under nurseryconditions. One year old seedlings of J. polycarpos raised in polybags filled with pottingmedia composed of soil, sand, and farmyard manure (2:1:1:) were externally givendifferent doses of vermicompost having six treatments to study their effect on seedlinggrowth and quality parameters. Significant differences were observed in shoot length,collar diameter, root length, number of roots, root and shoot biomass of J. polycarposseedlings raised in different potting media. Maximum growth of various seedlingparameters viz., shoot length (26.28 cm), root length (37.48 cm), collar diameter (4.61 mm)and number of roots (32.00) was recorded in treatment T 6 i.e. seedlings which were given5 g vermicompost/seedling whereas minimum growth of various seedling parameterswas recorded in treatment T 1 i.e., control where no external dose of vermicompost wasapplied. Maximum fresh shoot biomass (7.84 g seedling -1 ), fresh root biomass (2.83 gseedling -1 ), total fresh biomass (10.67 g seedling -1 ), dry shoot biomass (4.73 g seedling -1 ),dry root biomass (1.78 g seedling -1 ) and total dry biomass (6.51 g seedling -1 ) were alsorecorded in treatment T 6 . The maximum value of various seedling quality parametersviz., root shoot ratio (0.37), volume index (558.50), Quality index (0.77), and least value ofsturdy quotient (5.70) was also observed in seedlings that were given 5 g vermicompost/seedling. The study recommended the application of vermicompost @ 5 g seedling -1 forthe production of quality planting stock of Juniperus polycarpos in the nursery.